Ray tracing method in a 3D analysis of fiber-optic elements - Witkowski, J.S.; Grobelny, A. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
In this paper, a numerical analysis of algorithm of optical fiber systems with dimensions much larger than light wavelength has been presented. This algorithm can be used especially in the case of multimode fiber-optic elements. The presented technique of the analysis is based on the ray tracing method (RTM). Up to now, the RTM was widely used for an analysis of lens-systems. In this paper, a new possibility for this method in fiber optic elements analysis has been shown. The algorithm permits to determine thousands of ray traces simultaneously in a desired 3D area of an arbitrarily defined refractive index. This technique can be applied for a gradient index (GI), step index (SI) fibers, different types of optical couplers, etc. The algorithm has been extended to analyze dispersion properties and pulse shape evolution tracking along a fiber-optic system.
Optica Applicata, Vol. 38, 2008, nr 2, s. 281-294
Keywords: optyka; dispersion; optical fiber system; optical; pulse evolution; ray tracing method